Chagas disease in Switzerland: current situation, challenges and opportunities - Vincent Chollet; Elise Rapp; Mar Velarde-Rodriguez; Marina Gold; Pascal Mäser; Jan Fehr; Nora Monnier; Yves Jackson; Pedro Albajar-Viñas; Pablo M. De Salazar (Swiss Medical Weekly)
Chagas disease is a parasitic infection found mainly in continental Latin America. However, it is now present globally due to increasing international mobility and its lifelong persistence in the absence of timely treatment. In Switzerland, this neglected tropical disease presents a significant challenge because of its high potential for transmission, severe clinical manifestations and complications, and a lack of medical and public health programs at both the cantonal and national levels. This paper reviews the medical and public health interventions addressing Chagas disease in countries outside Latin America. It provides a specific perspective on the challenges, opportunities, and strategies for the elimination of Chagas disease as a public health problem within the Swiss context. This article concludes with the introduction of the newly created Swiss Chagas Network, which aims to develop strategies for improving the management of Chagas disease in Switzerland.